Implementation of Progressive Law in Enforcement of Environmental Law in Indonesia: The Current Problems and Future Challenges - Dewantara, Antonius Mahendra; Larasati, Dika Kirana (Faculty of Law, Universitas Negeri Semarang, 2022)
Law enforcement in the environmental sector has a broad dimension, not only related to aspects of material losses, aspects of state administration, but also aspects of criminal law. Enforcement in this sector even faces several challenges and obstacles, one of which concerns the various motives and perpetrators of environmental crimes that continue to grow. This study aims to analyze how progressive law should work and be applied in environmental law enforcement in Indonesia. This study highlighted that one of the ways to realize social justice for all Indonesian people as stated in the fourth paragraph of the Preamble to the 1945 Constitution of the Republic of Indonesia is to utilize existing natural resources for the welfare of society. Article 3 paragraph (3) of the 1945 Constitution of the Republic of Indonesia also mandates that the land, water and natural resources contained therein shall be controlled by the state and used as much as possible for the prosperity of the people. This study also confirms that according to many experts, progressive law is pro-justice and pro-people law. This means that in sentencing legal actors are required to prioritize honesty and sincerity in law enforcement. They must have empathy and concern for the suffering experienced by the people. Thus, the interests of the people, in this case welfare, must be the orientation and ultimate goal in administering law.